The triumph of technology - Broers, Alec, 1938- (Reith lectures ;, 2005)
Taken from the 2005 BBC Reith Lectures, and including a new introduction and conclusion, Alec Broers shows how technology drives our world today. Explaining how technologies emerged, he argues that if we use technology wisely it can improve our lives and provide solutions to current global problems.